Sosialiasi Manajemen Sistem Notifikasi Keberangkatan Jamaah Haji dan Umrah Secara Online di Kantor Kemenag Lhokseumawe - Kesuma Dinata, Rozzi; Sujacka Retno; Novia Hasdyna; T Irfan Fajri; Mutasar (Lembaga Dongan Dosen, 2023)
Currently, at the Ministry of Religious Affairs (Kemenag) office in Lhokseumawe, there is no online notification system available for the departure of Hajj and Umrah pilgrims. In the age of rapid advancements in information technology, the importance of an online notification system is increasing, as it can facilitate the departure process for Hajj and Umrah pilgrims. The objective of this community engagement activity is to provide socialization to the staff in the Hajj and Umrah department at the Ministry of Religious Affairs (Kemenag) in Lhokseumawe. The primary focus is on enhancing their understanding of the online notification system, as part of an ongoing effort to improve the efficiency and transparency in the online departure process for Hajj and Umrah pilgrims at the Kemenag office in Lhokseumawe.